Coherence lengths and quantum entanglement in radiative capture reactions - Mehdi Mirzaee; Hossein Sadeghi (Scientific Reports)
Abstract Coherence length ( $$L_c$$ ) is a key concept in quantum mechanics, representing the ability of a quantum system to maintain well-defined phase relationships over time. This paper investigates the relationship between coherence length, decay width ( $$Γ$$ ), and atomic mass in radiative capture reactions using a machine learning model. Additionally, the quantum entanglement of the resulting states is quantified using the von Neumann entropy. The results demonstrate the inverse relationship between coherence length and decay width, highlighting the universal nature of this relationship across various reactions. The findings provide valuable insights into the behavior of particles in radiative capture reactions and have implications for both experimental and theoretical studies in nuclear and particle physics.